Discrimination in Latin America : An Economic Perspective - Nopo, Hugo; Chong, Alberto; Moro, Andrea (Washington, DC: Inter-American Development Bank and World Bank, 2012)
The chapters presented in this volume adopt a variety of these methodological tools in order to explore the extent to which discrimination against women and demographic minorities is pervasive in Latin America. In chapter two, Castillo, Petrie, and Torero present a series of experiments to understand the nature of discrimination in urban Lima, Peru. They design and apply experiments that exploit degrees of information on performance as a way to assess how personal characteristics affect how people sort into groups. Along similar lines, in chapter three, Cardenas and his research team use an experimental field approach in Colombia to better understand pro-social preferences and behavior of both individuals involved in the provision of social services (public servants) and potential beneficiaries of those services (the poor). In chapter four, Elias, Elias, and Ronconi try to understand social status and race during adolescence in Argentina. They asked high school students to select and rank ten classmates with whom they would like to form a team and use this information to construct a measure of popularity. In chapters five and six, Bravo, Sanhueza, and Urzua present two studies covering different aspects of the labor market using different methodological tools. Based on an audit study by mail, their first study attempts to detect gender, social class, and neighborhood of residence discrimination in hiring practices by Chilean fir. In a second study, they use a structural model to analyze gender differences in the Chilean labor market. In chapter seven, Soruco, Piani, and Rossi measure and analyze possible discriminatory behaviors against international emigrants and their families remaining in southern Ecuador (the city of Cuenca and the rural canton of San Fernando). Finally, in chapter eight, Gandelman, Gandelman, and Rothschild use micro data on judicial proceedings in Uruguay and present evidence that female defendants receive a more favorable treatment in courts than male defendants.